Load trains as essential services: the brazilian railways and the pandemic: - de Fátima Rossone Alves, Jéssica; Hirt, Carla (Geografares, 2021)
This article presents a critique of transport operated on Brazilian railways during the COVID-19 pandemic. Starting from a historical-structural perspective, it analyzes the hegemonic model of railway transport production in Brazil, discusses the consequences of this model in the territories and presents the policies prioritized by the Brazilian State in the pandemic situation, which are fundamental in guaranteeing the neoliberal order, conditioning territorial planning and railway infrastructure management. From this reading, it is clear that Brazil could have found in these infrastructures a logistical alternative to face the pandemic, if the political option and their management were different.
Keywords: Brazilian railroads; Territory; COVID-19 Pandemic